Gambaran Persepsi Pengawas terhadap Efektivitas Geotab dalam Mengendalikan Risiko Kecelakaan Kendaraan Ringan di Divisi X - Zafirah, Aisyah Yasmin; Satrya, Chandra (UI Scholars Hub, 2024)
This study aims to understand supervisors' perceptions of the effectiveness of Geotab as a control measure for mitigating the risk of collisions involving light vehicles. Conducted in Division X of PT. X, a mining industry, from February to June 2023, this descriptive, semi-qualitative study collected data through control effectiveness questionnaires, interviews, and document review. The variables studied include the relevance, coverage, reliability, reactivity, resource competence, and supervision system of Geotab. Questionnaire results showed supervisor perception scores of 3.09 for relevance (appropriate), 3.10 for coverage (appropriate), 3.06 for reliability (appropriate), 2.99 for reactivity (appropriate), 2.93 for resource competence, and 2.95 for the supervision system (appropriate). Interview results highlighted keywords such as